Energy Spectra Near Ganymede From Juno Data. Issue 10 (21st May 2021) - Paranicas, C.; Szalay, J. R.; Mauk, B. H.; Clark, G.; Kollmann, P.; Haggerty, D. K.; Westlake, J.; Allegrini, F.; Ebert, R. W.; Connerney, J. E. P.; Bolton, S.
Abstract: The moon Ganymede has a strong internally generated magnetic field that separates the surface into two regions, with the polar surface magnetically connected to the Jovian environment. Consequently, the weathering of Ganymede's surface by plasma and energetic charged particles trapped in the Jovian magnetosphere is not uniform. At the same time, optical data suggest differences in the surface ice between the poles and the equator, with further refinements in the equatorial surface that have a longitudinal dependence. Here, we use Juno spacecraft data to characterize the charged particle environment along Ganymede's orbit (from about 50 eV to 1 MeV for electrons and 10 eV to 6 MeV for protons). These results put us into a better position to test the hypothesis that space weathering by electrons causes the brighter poles of Ganymede, given that electron fluxes are likely to be more clearly separated between the polar and equatorial regions. Plain Language Summary: Electron weathering of ice may be the reason Ganymede's poles are brighter. These particles are well separated by the two magnetic topologies of Ganymede, whereas ions are not as well separated. We suggest ions may be converted to energetic neutral atoms near Ganymede and reach the surface despite the magnetic barrier. We quantify the environmental inputs in this paper. Key Points: Juno orbital evolution has allowed better characterization of the region near Jupiter's magnetic equator and Ganymede's orbital distance Electron and proton energy spectra from that region derived from Jovian Auroral Distributions Experiment (JADE) and Jupiter Energetic‐particle Detector Instrument (JEDI) data are presented We propose that polar versus equatorial albedo differences on Ganymede are due to changes resulting from electron precipitation